The Use of Google Sites to Display Archival Information at the NTB Province Representative BPK - Tahir, Fahruddin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
For government organizations, good archive management not only has an important role in decision making, but is also an obligation that must be carried out by each government organization itself. However, the archive information displayed so far is still in the form of tables in Microsoft Excel which are less informative and need to be reprocessed by users to be able to obtain the information needed related to archives in the government organization. This research aims to produce archival information media through Google Sites that is more informative, interesting, and easily accessible for users in the BPK Representative of West Nusa Tenggara Province. With this media, it is expected that the archival function in helping decision making by government organizations can be achieved.